PERANCANGAN SISTEM INFORMASI PENJUALAN PADA YOURSBEAUTY STORE KOTA JAMBI BERBASIS WEBSITE - Gunardi Gunardi; Ayu Feranika; Ronald Naibaho; Bayu Perdana (Universitas Methodist Indonesia, 2023)
YoursBeauty is one of the business ventures engaged in sales that still uses notebooks and agendas. YoursBeauty Jambi City is located at Jalan Amir Hamzah No.76, Sungai Kambang, Jambi. In the process of managing sales data and making reports using notes for sales and agenda books for sales reports. YoursBeauty Jambi City carries out promotional activities and product buying and selling transactions are carried out by requiring customers or buyers from far away to come just to find out what products are offered, besides those customers cannot place orders remotely to choose what products to buy, as well as promoting word of mouth and social media such as Instagram. Therefore, this study aims to provide solutions to problems that occur by offering sales applications using a programming language, namely PHP and MySQL database where the system development is using the waterfall method and using a unified model language system model approach using use case diagrams, activity diagrams, class diagrams and flowchart diagrams. Providing convenience for the store in providing the latest product information and services provided by the YoursBeauty store, the new system produces output that displays structured sales data and cost data and displays the required reports to facilitate YoursBeauty Jambi City in data processing.